SCALLOPED interacts with YORKIE, the nuclear effector of the hippo tumor-suppressor pathway in Drosophila. - Goulev, Y.; Fauny, J.D.; Gonzalez-Marti, B.; Flagiello, D.; Silber, J.; Zider, A. (Current Biology, 2008)
In Drosophila, SCALLOPED (SD) belongs to a family of evolutionarily conserved proteins characterized by the presence of a TEA/ATTS DNA-binding domain [1, 2]. SD physically interacts with the product of the vestigial (vg) gene, where the dimer functions as a master gene controlling wing formation [3, 4]. The VG-SD dimer activates the transcription of several specific wing genes, including sd and vg themselves [5, 6]. The dimer drives cell-cycle progression by inducing expression of the dE2F1 transcription factor [7], which regulates genes involved in DNA replication and cell-cycle progression. Recently, YORKIE (YKI) was identified as a transcriptional coactivator that is the downstream effector of the Hippo signaling pathway, which controls cell proliferation and apoptosis in Drosophila[8]. We identified SD as a partner for YKI. We show that interaction between YKI and SD increases SD transcriptional activity both ex vivo in Drosophila S2 cells and in vivo in Drosophila wing discs and promotes YKI nuclear localization. We also show that YKI overexpression induces vg and dE2F1 expression and that proliferation induced by YKI or by a dominant-negative form of FAT in wing disc is significantly reduced in a sd hypomorphic mutant context. Contrary to YKI, SD is not required in all imaginal tissues. This indicates that YKI-SD interaction acts in a tissue-specific fashion and that other YKI partners must exist.